Make the Academy Great Again: Right-Wing Think Tanks and the 'Crisis' in Universities - Scatamburlo-D’Annibale, Valerie L (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
In recent years, there has been an increase in reports declaring Canadian universities are suffering from a ‘viewpoint diversity crisis’ that purportedly compromises their ability to serve as bastions of open inquiry. This article contextualizes this narrative, tracing its historical roots and examining its production within a right-wing infrastructure that has long targeted the academy and sought to undermine public faith in higher education to further an ideological agenda reflective of Friedrich Hayek’s reverence for free market fundamentalism and concomitant contempt for social justice. To the degree that universities are imperiled as proponents of viewpoint diversity claim, the tangible threat stems from externally coordinated assaults on academe and not the contrived crisis projected onto it.